Emergency Department Frequent User: Pilot Study of Intensive Case Management to Reduce Visits and Computed Tomography - Grover, Casey A; Close, Reb JH; Villarreal, Kathy; Goldman, Lee M (Western Journal of Emergency Medicine, 2010)
Objective: Emergency department (ED) frequent users account for a large number of annual ED visits and often receive radiological studies as a part of their evaluation. We report a pilot study of a case management program for ED frequent users to reduce ED usage and radiation exposure.Methods: This observational retrospective study was performed at a community hospital ED. Between May 2006 and April 2008, 96 patients were enrolled in a case management program and were followed through November 2008. The case management program consisted of a multi-disciplinary team of physicians, nurses, social services and specialists in pain management and behavioral health. Patients were enrolled if they had five or more visits to the ED in the previous month, if a concern about a patient’s ED use was raised by staff, or if they were identified by the California prescription monitoring program. Case management addressed specific patient issues and assisted with receiving consistent outpatient care. The number of ED visits per patient and the number of radiological studies at each of these visits was recorded. When reviewing data for analysis, we used the number of total images in all computed tomography (CT) scans during the given time period.Results: In the six months prior to enrollment, patients averaged 2.3 ED visits per patient per month. In the six months after enrollment, patients averaged 0.6 ED visits per patient per month (P<0.0001), and all visits after enrollment up to November 2008 averaged 0.4 visits per patient per month (P<0.0001). In the six months prior to enrollment, these patients averaged 25.6 CT images per patient per month. In the six months after enrollment, patients averaged 10.2 CT images per patient per month (P=0.001), and all CT images after enrollment up to November 2008 averaged 8.1 CT images per patient per month (P=0.0001). This represents a decrease in ED use by 83% and a decrease in radiation exposure by 67%.Conclusion: Case management can significantly reduce ED use by frequent users, and can also decrease radiation exposure from diagnostic imaging. [West J Emerg Med. 2010; 11(4): 336-343].